Culturas populares no presente: fomento, salvaguarda e devoração - Ikeda, Alberto T. [UNESP] (Universidade de São Paulo (USP), Instituto de Estudos Avançados, 2013)
The paper proposes reflections about the presence of popular and traditional cultures in the scene of contemporary Brazil's culture, from the resurgence of a movement interested in expressions of music, dances and parties especially between the 20th and 21st centuries.

O ensaio propõe reflexões em torno da presença das culturas populares de tradição oral no cenário da cultura contemporânea do Brasil, a partir do ressurgimento de um intenso movimento de interesse por expressões de músicas, danças e festas tradicionais, sobretudo, no entremeio dos séculos XX e XXI.
Promoting, safeguarding and devouring contemporary popular cultures
Keywords: Cultura popular; Folclore; Salvaguarda; Devoração cultural; Popular culture; Folklore; Safeguard; Cultural devouring